Moving towards a "COAL-PEC"? - Clemens Haftendorn; Christian von Hirschhausen; Franziska Holz (Weekly Report, 2008)
Coal has for many years been considered as a resource of the past and as a result its importance has been underestimated. Yet coal still is the main pillar for generating electricity in most countries: A quarter of the worldwide primary energy consumption is provided by coal. While the world's largest coal producers, China, the USA and India, are at the same time the largest consumers of coal. Smaller producers and consumers of coal engage extensively in international trade. In particular the seaborne coal trade has increased significantly since the 1990's. In the past two years prices of import coal also have increased considerably. In September 2008, importers in Europe had to pay prices of more than 200 US dollars per ton, a price level many times higher than the historical average. In this context, fears have increasingly been voiced that the international coal market - analogous to the oil market which continues to be dominated by the OPEC-might witness the emergence of a supplier cartel, a "COAL-PEC". A strong tendency towards the concentration of companies has in fact been observed in the international coal market in the past years. Increased prices could have resulted from the use of market power. Drivers for the price increase were the strong rise in demand, in particular from China and India, capacity bottlenecks in production and shipment as well as a lack of investments. In the future a tight market and high coal prices have to be expected.
Keywords: L11; L72; C69; 330; Coal; Energy; Market structure; Simulation model